Praktek Cuci Tangan Pakai Sabun di Sekolah pada Siswa Sekolah Dasar di Kota Semarang - Nugraheni, Hermien; Widjanarko, Bagoes; Cahyo, Kusyogo (Jurnal Promosi Kesehatan Indonesia, 2010)
PHBS in school applying an absolute necessity as the emergence of diseases, which was generally associated with PHBS, especially associated with the practice of washing hands with soap, as an indicator PHBS in educational institutions. The aims of research are identify the factors that associated with practice of hand washing (CTPS) in the elementary school students Semarang City. This research is explanatory research with Cross Sectional design. Research sample is 5th grade elementary school students in the Semarang city with sample retrieval technique with proportional simple random sampling of 394 respondents. Retrieval of data has conducting interview. The results of bivariate analysis using chi square test showed there are three variables which significantly associated with, they are the role of parenting, the role of teachers in schools and the availability of the practice of hand washing at the elementary school students. Logistic regression test results, then gained, variables that jointly associated with the practice of hand washing at the elementary school students are the role of parenting and the availability of the practice of hand washing at the elementary school. The most dominant variables associated with the practice of hand washing at the elementary school students is the availability of hand washing facilities in schools, where the availability of hand washing facilities in schools that both have probably 20 times the practice of washing hands with soap in school of the availability of hand washing facilities are not good.